PENGARUH DOSIS ECO-ENZYME DAN JENIS PUPUK KANDANG TERHADAP SERAPAN NITROGEN, PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN JEPANG (Cucumis sativus var. roberto) - muhibbatul lubabah; Agus Sugianto; Djuhari Djuhari (AGRONISMA, 2022)
Cucumber is one of the potential agricultural commodities because it has good market opportunities. However, this is not supported by the low production of cucumbers. One effort to optimize the yield potential of cucumbers is to increase the ability of the soil to support plant growth by adding organic matter such as manure and eco-enzyme. The aim of this study was to determine the interaction between the dose of eco-enzyme and the type of manure on N uptake, growth and yield of Japanese cucumber (Cucumis sativus var. roberto). The study was conducted using a Factorial Randomized Block Design (RAK) experiment consisting of 2 factors. First factor, is the type of manure (P) consisting of 3 levels, namely P1 (Cow Manure), P2 (Goat Manure) and P3 (Chicken Manure). Second Factor consists of 3 levels, namely E1 (Eco-enzyme dose 3 L/ha), E2 (Eco-enzyme dose 6 L/ha) and E3 (Eco-enzyme dose 9 L/ha). There were 9 treatment combinations with each treatment repeated 3 times with 3 plant samples, so that 81 experimental units were obtained. Data analysis used 5% ANOVA, if it was real, it was continued with 5% BNJ. The results showed that a good trend was found in the combination of P2E2 (Goat manure with eco-enzyme dose of 6 L/ha) on all growth variables and yields of Japanese cucumbers except for leaf area 28 days after planting and fruit weight yield.Â Keywords : Japanese cucumber, Dosage of eco-enzyme, animal manure